Autorização para Terminal Portuário de Uso Privado (TUP) na Lei nº 12.815/2013 - Lambauer, Roberto Zilsch (2016)
This paper deals with the legal framework applicable to authorizations for private port terminals issued under Law No. 12,815/2013 and applicable regulation, notably Federal Decree No. 8,033/2013 and Resolution No. 3,290/2014, issued by the National Agency for Waterway Transportation ANTAQ. The paper identifies the origin of the authorization in the port sector and the use of said grant mechanism to increase competition between public and private port terminals. After commenting on the context in which Law No. 12,815/2013 was enacted, we address the criteria distinguishing the authorization from the other types of contracts provided in the referred law. The study emphasizes the procedure for the grant of authorization and the rules applicable to the Adhesion Contract. It also deals with controversial issues such as the grant of easement and access to third parties and the payment of indemnification in case of early termination of the grant. Finally, we analyze whether operators that were granted authorization under the previous legal framework in areas located in public ports have acquired right to remain under the same arrangement